Evaluation of taurine content on skeletal muscle of exercised rats using MALDI-TOF MS imaging analysis - Riho Komatsuzawa; Teruo Miyazaki; Hajime Ohmori; Chitose Maruyama; Stephen W. Schaffer; Shigeru Murakami; Takashi Ito (Japanese Society of Physical Fitness and Sports Medicine, 2020)
The amount of taurine and taurine derivatives in the body is affected by various diseases and physiological events, such as exercise. However, there is little information about possible changes in taurine distribution within tissue. In the present study, we examined whether matrix-assisted laser desorption/ionization-imaging mass spectrometry (MALDI-IMS) can be used to determine the effect of exercise on the distribution and content of taurine and acetyltaurine, a taurine derivative present in skeletal muscle. Using 9-aminoacridine to detect the amino acids in tissue samples, the content of taurine and acetyltaurine in homogenates of skeletal muscle was measured by MALDI-IMS. While the intrinsic levels of taurine in skeletal muscle tissue were adequate to be detected by MALDI-IMS, that of acetyltaurine was not observed. Following 120-min of treadmill running (20m/min), taurine content of soleus and plantaris muscles significantly declined. In the gastrocnemius muscle, taurine content is higher in slow-twitch fiber than fast-twitch fiber. However, the taurine content was not significantly changed by treadmill running in both fast- and slow-twitch fiber of the gastrocnemius muscle. In conclusion, MALDI-IMS using 9-aminoacridine as a matrix could detect the distribution of taurine in skeletal muscle before and after exercise.